Effects on radial growth rate on basic density and compressive strength in 10-year-old Swietenia macrophylla planted in South Kalimantan, Indonesia - Anak Agung Ayu Ratih Frismanti; Wiwin Tyas Istikowati; Ikumi Nezu; Jyunichi Ohshima; Shinso Yokota; Futoshi Ishiguri (Forest Science and Technology, 2025)
To evaluate the effect of radial growth rate on wood properties (basic density and compressive strength parallel to the grain under green conditions), standing tree characteristics (stem diameter, tree height, and stress-wave velocity of stems) were determined for 50 trees of 10-year-old Swietenia macrophylla G. King planted in South Kalimantan, Indonesia. The trees were classified into three categories (fast-, medium-, and slow-growth) based on the stem diameter. Radial variations of basic density and compressive strength parallel to the grain under green conditions were also determined for 15 selected trees (five trees in each radial growth category). The mean values of standing trees were 24.4 cm for stem diameter at 1.3 m above the ground, 20.4 m for tree height, and 3.53 km s−1 for the stress-wave velocity of stems. The mean values of basic density and compressive strength were 0.49 g cm−3 and 36.1 MPa, respectively. Results from intercept-only linear mixed-effects modeling indicated that the effect of radial growth rate on wood properties was limited. Based on the results of nonlinear mixed effect modeling, radial variations of basic density and compressive strength were well adapted to the exponential term with the Michaelis-Menten equation with a random effect of growth category and the logarithmic equation without a random effect, respectively. Thus, basic density initially decreased from the pith, reached a minimum, and then increased toward the bark, whereas compressive strength decreased and then stabilized. In addition, no significant correlations were found between growth characteristics and wood properties with an exception, suggesting that the negative effects of radial growth rate on wood properties of this species might be limited. This tendency may enable the maximization of productivity and the quality of the wood. Thus, tree breeding programs to improve the wood quality of this species can be established in Indonesia.